Riding the Waves of Fluctuating Oil Prices: Decoding the Impact on Economic Growth - Triantoro, Arvian; Akhtar, Muhammad Zaheer; Khan, Shiraz; Zaman, Khalid; Khan, Haroon ur Rashid; Pathath, Abdul Wahab; Mahmad, Muhamad Amar; Sertoglu, Kamil (International Journal of Energy Economics and Policy, 2023)
Oil price fluctuations have always been controversial and remain significant in how a country’s economy develops. It is especially easy for the worldwide price of natural resources to fluctuate, putting developing nations at risk of economic instability. Consider Pakistan’s economy, which is very sensitive to changes in oil prices due to its reliance on the commodity. This research analyses the effects of oil prices on several macroeconomic indicators, including inflation, imports, gross savings, domestic lending to the private sector (DCPS), and industrial value-added in Pakistan. The study uses an error-correcting framework known as autoregressive distributed lag (ARDL) modelling to examine long-term connections between variables and their short-term implications. Additionally, data acquired between 1970 and 2020 was analyzed using Granger causality tests, impulse response functions (IRFs), and variance decomposition analyses (VDAs). The study found that inflation and domestic loans to the private sector hampered economic development in the near run. Conversely, imports, gross savings, industrial value added, and oil rents have a positive effect. A long-term connection between these variables was verified using the boundaries test. A unidirectional link was found in the causality tests between economic growth and imports, inflation and economic growth, and gross saving and domestic credit. An inverse link between domestic credit and inflation was found. The effect of oil rents on economic development in Pakistan is expected to rise during the next four years, according to the forecasts, before levelling out. According to the VDA results, the most critical factor influencing Pakistan’s economic development over the next decade would be domestic lending to the private sector. Following these empirical results, the study proposes policy adjustments that might help Pakistan’s economy expand more quickly and sustainably.